Single Molecule Blinking and Photobleaching Separated by Wide-Field Fluorescence Microscopy - Gensch, Thomas (2005)
Single molecule fluorescence detection of Atto590 in poly(vinyl alcohol) was achieved by using a wide-field epifluorescence microscope with CCD-camera detection. Image sequences are obtained from which the time traces of the detected molecules are built. We find a distinctive difference between the time evolution of the fluorescence originating from the molecules detected in the first image of the sequence compared to the time evolution of the fluorescence of the molecules detected in each image of the sequence. Atto590 shows very long blinking times and photobleaching and photoblinking that are both quadratically dependent on the irradiation power density. Our approach allows kinetic separation of photobleaching from blinking. The possibility of choosing different ensembles of molecules is demonstrated and taken advantage of for this aim. Initially dark molecules or low emitting ones that might be overlooked are important to describe the complete ensemble behavior.